TRAFICO DE PESSOAS E A PROSTITUIÇÃO: ASPECTOS DE UMA PROFISSÃO ANTIGA E DE UM PROBLEMA ATUAL (Reflection and Critique Law Magazine, 2019)
The present work aims at the study human trafficking, with a focus on exploration for sexual purposes, seeking to conceptualize the verb, as well as explaining the legislation applied in Brazil and the form that such a crime is practiced. Briefly, it can be stated that human trafficking is a crime that has occurred in the world for decades, however, there is no open talk in society on the subject, a situation that ends up favoring gangs, facilitating the application of the blows on the victims, these being completely deluded and deceived by the criminals. One of the most important laws on the subject is the protocol of Palermo that deals with this crime and provides provisions for prevention, repression and reception of victims and has an international scope. After many years in arrears, Brazil supplied it with the creation of Law 13344/2016, which deals with the crime of trafficking in persons. Thus, it appears that the country has made progress with the creation of said law, but it is not something to be celebrated, since there is still a significant number of human trafficking every year.